A Rare Case of Urogenital Myiasis in a 49-Year-Old Woman. (1st April 2022) - Salehi, Amir Mohammad; Jenabi, Ensiyeh; Salehi, Maral
Abstract : Myiasis refers to the infestation of living vertebrae with fly larvae, principally occurring in individuals with a low socioeconomic status and poor personal hygiene. Myiasis is rarely manifested in the urogenital system. Herein, we report a case of urogenital myiasis in a 49-year-old rural woman complaining of maggots in the urine and severe genital itching.